KONSEP DAN MODEL MADRASAH UNGGUL : MENJAWAB TANTANGAN PASAR GLOBAL - Bahrudin Salim (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the concept and model of superior madrasah that are able to answer the challenges of today's global market. This research model is library research using qualitative research methods where the results are in the form of criteria for superior madrasah models and aspects of change towards these madrasah. The research results show that the criteria for a superior madrasah model are appropriate to the challenges market global is madrasah which still maintain its specialty as an Islamic boarding school (pesantren) mouthpiece accompanied addition eye lessons with teacher criteria as already researcher convey, and infrastructure including teaching materials and output which no only ready fill in field work but also capable think critical, creative, innovative, own spirit and ability entrepreneurshipand skilled in digital or native digital. To realize this madrasah, it is necessary to change with carry out a strategy of keeping old things that are good and adopting new things that are better, both regarding the quality of teachers, curriculum, teaching materials and regulations or other things that need to be followed up accordingly researcher recommendations